2006
DOI: 10.1002/adma.200601551
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Lubricating Nano‐Ball‐Bearings

Abstract: Cubic symmetry in octasilsesquioxanes ([RSiO 1.5 ] 8 , diameter 1 nm) places functionality in each octant in Cartesian space, enabling nanometer-scale construction of materials with subtle tailoring of global properties. [1][2][3] Diverse studies of OPS (octasilsesquioxanes) range from their ordering in solids (nanocomposites) to catalysts, NMR standards, and spacecraft coatings. [4][5][6][7][8][9][10][11][12][13] The prototypical OPS [10] (R = phenyl) is air-stable to temperatures above 500°C; however, high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Increase in the surface roughness reduces the real area of contact between the AFM probe and the surface, thereby reducing the observed friction. Some authors have suggested a self-lubricating ''nano ball bearing'' mechanism for low friction nanomaterials, including POSS, 42 diamond nanoparticles, 43 and fullerene-like inorganic nanoparticles. 44 Nanoscale friction characteristics are also significantly influenced by the magnitude of the adhesive force between the AFM probe and the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Increase in the surface roughness reduces the real area of contact between the AFM probe and the surface, thereby reducing the observed friction. Some authors have suggested a self-lubricating ''nano ball bearing'' mechanism for low friction nanomaterials, including POSS, 42 diamond nanoparticles, 43 and fullerene-like inorganic nanoparticles. 44 Nanoscale friction characteristics are also significantly influenced by the magnitude of the adhesive force between the AFM probe and the surface.…”
Section: Resultsmentioning
confidence: 99%
“…13 C NMR spectra were collected at 150.9 MHz with a 36,057.7-Hz spectral width. 29 Si NMR spectra were collected at 119.2 MHz with a 9566.3-Hz spectra width.…”
Section: Instrumentationmentioning
confidence: 99%
“…The meta-substituted sulfonylation was confirmed by FT-IR, 1 H NMR, and 13 C NMR spectroscopy. 29 Si NMR spectroscopy and MALDI-TOF mass analysis were used to determine the degree of substitution in the reaction. The 29 Si NMR spectra of the compounds confirmed their complete conversion from the parent OPS.…”
Section: Characterization Of Omdpssmentioning
confidence: 99%
See 2 more Smart Citations